Appendicitis risk prediction models in children presenting with right iliac fossa pain (RIFT study): a prospective, multicentre validation study. (April 2020) - ,; Nepogodiev, Dmitri; Wilkin, Richard JW; Bradshaw, Catherine J; Skerritt, Clare; Ball, Alasdair; Moni-Nwinia, Waaka; Blanco-Colino, Ruth; Chauhan, Priyesh; Drake, Thomas M; Frasson, Matteo; Gee, Oliver; et al.
Summary: Background: Acute appendicitis is the most common surgical emergency in children. Differentiation of acute appendicitis from conditions that do not require operative management can be challenging in children. This study aimed to identify the optimum risk prediction model to stratify acute appendicitis risk in children. Methods: We did a rapid review to identify acute appendicitis risk prediction models. A prospective, multicentre cohort study was then done to evaluate performance of these models. Children (aged 5–15 years) presenting with acute right iliac fossa pain in the UK and Ireland were included. For each model, score cutoff thresholds were systematically varied to identify the best achievable specificity while maintaining a failure rate (ie, proportion of patients identified as low risk who had acute appendicitis) less than 5%. The normal appendicectomy rate was the proportion of resected appendixes found to be normal on histopathological examination. Findings: 15 risk prediction models were identified that could be assessed. The cohort study enrolled 1827 children from 139 centres, of whom 630 (34·5%) underwent appendicectomy. The normal appendicectomy rate was 15·9% (100 of 630 patients). The Shera score was the best performing model, with an area under the curve of 0·84 (95% CI 0·82–0·86). Applying score cutoffs of 3 points or lower for children aged 5–10 years and girls aged 11–15 years, and 2 points or lower for boys aged 11–15 years, the failure rate was 3·3% (95% CI 2·0–5·2; 18 of 539 patients), specificity was 44·3% (95% CI 41·4–47·2; 521 of 1176), and positive predictive value was 41·4% (38·5–44·4; 463 of 1118). Positive predictive value for the Shera score with a cutoff of 6 points or lower (72·6%, 67·4–77·4) was similar to that of ultrasound scan (75·0%, 65·3–83·1). Interpretation: The Shera score has the potential to identify a large group of children at low risk of acute appendicitis who could be considered for early discharge. Risk scoring does not identify children who should proceed directly to surgery. Medium-risk and high-risk children should undergo routine preoperative ultrasound imaging by operators trained to assess for acute appendicitis, and MRI or low-dose CT if uncertainty remains. Funding: None.